Vegetative propagation of Isau (Dimocarpus Longana var. Malesianus Leenh.) by cuttings - Bili, Geraldine William (Universiti Malaysia Sarawak (UNIMAS), 2006)
Dimocarpus longana var. malesianus or isau is from the family Sapindaceae produces fruit like longan and has potential for commercialization. The species is indigenous to Sarawak. Currently there is not much of planting of isau outside its natural habitat along river banks partly due to scarcity of true-to-type planting material. This study was initiated to investigate the possibility of propagating isau by vegetative means. The results from the study on propagation by ttings showed that there were no significant differences in the various media and rooting hormones used. However, from observations, it appeared that peat and IBA 2g!L were the more effective rooting medium and rooting hormone RSpectively. Result of this study also revealed that cuttings obtained from young seedling plants were more readily to root as compared to those obtained from softwood or young shoots of mature trees. In the attempt of micropropagation by the in vitro technique, it was found that pruning to induce sprouting of new shoots and spraying of streptomycin onto Ibese new shoots prior to collecting them for use as eX81ants material were measures effective in reducing contamination in the shoot-tip and axillary explants. Clorox T at 25% was found to be effective in resulting higher Dumber ofgreen and contamination-free shoot-tips explants. Elongation of shoot-tip explants was observed a week after initiation ofculture in B5 medium without supplement of any plant growth regulators.